The Islamization of Southern Kalimantan: Sufi Spiritualism, Ethnic Identity, Political Activism - Chalmers, Ian (Studia Islamika, 2007)
Sufism was the first form of Islam to be brought to Kalimantan, as was the case throughout most of Southeast Asia. Increasing numbers of Muslim traders and itinerant Sufi preachers came to the Indies from the 13th century onwards, and by the 16th century Islam had become a significant presence throughout the archipelago, especially in port cities and elsewhere on the coast. The popularity of Sufism grew rapidly in the 18th and 19th centuries as increasing numbers of the faithful returned from the pilgrimage (haj) to Medina and Mecca, bringing the faith back with them to various communities scattered throughout the islands' This growth in the numbers of pilgrims (haji) had direct political significance, for they had inevitably come into contact with new religio-political ideas while in the Holy Land.DOI: 10.15408/sdi.v14i3.542